Competencies and (Global) Talent Management - Machado, Carolina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book covers the main issues on the study of competencies and talent management in modern and competitive organizations. The chapters show how organizations around the world are facing (global) talent management challenges and give the reader information on the latest research activity related to that. Innovative theories and strategies are reported in this book, which provides an interdisciplinary exchange of information, ideas and opinions about the workplace challenges.
Talent management -- Global talent management -- Competencies management -- Performance management -- HRM Policies and practices -- Career management -- Training and development -- Coaching -- Mentoring -- Culture and organizational behavior -- Work changes -- Workforce behavior -- Strategic management -- Entrepreneurship.
Keywords: Industrial Management; Business; Management science; Education, Higher; Industrial Management; Business and Management; Higher Education